The glandulous Specklinia: morphological convergence versus phylogenetic divergence - Karremans, Adam; Bogarín, Diego; Pupulin, Franco; Luer, Carlyle; Gravendeel, Barbara (Phytotaxa, 2015)
The present paper focuses on the systematics of the Specklinia glandulosa species complex. Traditionally, S. glandulosa has been considered a widely distributed and variable species, ranging from Mexico to the Guiana Shield. Here it is treated as one of at least six different, albeit closely related, species. Of these species, S. pertenuis and S. vittariifolia, are recognized as distinct species and removed from the synonymy of S. glandulosa, and S. alajuelensis and S. gersonii are described and illustrated as new to science. Specklinia chontalensis is described and illustrated from living, Costa Rican material. Specklinia alajuelensis is compared with S. glandulosa and S. vittariifolia, from which it differs in its broader leaves, multi-flowered, lax inflorescence that surpasses the leaves, and smaller petals and sepals. Specklinia gersonii is compared with S. glandulosa, from which it differs in the smaller leaves, and the smaller, orange flowers.